Peripapillary retinal nerve fibre layer thickness and its association with refractive error in Chinese children: the Anyang Childhood Eye Study. (20th May 2016) - Kang, Meng‐Tian; Li, Shi‐Ming; Li, He; Li, Lei; Li, Si‐Yuan; Zhu, Bi‐Dan; Guo, Yi‐Qin; Meng, Bo; Sun, Yun‐Yun; Ran, Anran; Wang, Yi‐Peng; Liu, Luo‐Ru; et al.
Abstract: Background: To report the thickness of the peripapillary retinal nerve fibre layer (pRNFL) in Chinese children and examine its association with refractive error, axial length (AL) and optic disc parameters. Design: Population‐based cross‐sectional study. Participants: A total of 2893 seven‐year‐old children from 11 randomly selected primary schools in Anyang, central China. Methods: Participants underwent ophthalmic examinations including optical biometry, cycloplegic autorefraction and spectral‐domain ocular coherence tomography. Main Outcome Measures: Retinal nerve fibre layer thickness in 16 radial sections, cycloplegic spherical equivalent, AL. Results: The mean (SD) average RNFL thickness was 102.01(8.02) µm. The average RNFL thickness decreased with smaller disc area ( r  = 0.18, R 2  = 0.03, P  < 0.0001), bigger cup area ( r  = −0.11, R 2  = 0.01, P  < 0.0001), smaller rim area ( r  = 0.28, R 2  = 0.08, P  < 0.0001), smaller nerve head volume ( r  = 0.27, R 2  = 0.07, P  < 0.0001), longer AL ( r  = −0.15, R 2  = 0.02, P  < 0.0001) and a negative spherical equivalent ( r  = 0.11, R 2  = 0.01, P  < 0.0001). Hyperopic children had a thicker RNFL than emmetropic children [102.45(8.13) µm vs . 100.81 (7.18) µm, P  < 0.001]. Myopic children had thinner RNFL than emmetropic children [99.17 (7.69) µm vs . 100.81 (7.18) µm, P  < 0.05]. Conclusion: Retinal nerve fibre layer thickness decreased with increasing AL, higher myopia, bigger cup area, smaller disc and rim area, and a smaller nerve head volume, but the coefficient of determination for all these associations was small. The RNFL in myopes was significantly thinner than emmetropes or hyperopes, but with small absolute differences. The study provides RNFL values for healthy 7‐year‐old Chinese children. Follow up of this cohort to observe the change of RNFL thickness with myopia and possible change in detected associations with age is planned.